Islam in North Sumatra: Study on the Naqsabandiyah Sufi Order in the Malay Langkat Community - Azhar Azhar; Suryo Adi Sahfutra (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2022)
This research focuses on the development of Islamic Da'wa in the Malay Langkat community, particularly during the early period of Islam developed by Tarekat Naqsabandiyah. Using a social historical approach, this study produced several findings. The historical data regarding the initial entry of Islam indicates two arguments, one originating from Barus and the other from Peurlak. However, the strongest argument for the entry of Islam into Langkat comes from the Aceh Peurlak region. The history of Islamic Da'wa is marked by several events, such as the establishment of the Azizi Grand Mosque, the Masrulah Madrasah, and the Babussalam Besilam Suluk settlement, which has historical connections with the followers of Tarekat Naqsabandiyah in Malaysia. After Indonesia's independence, the social and religious conditions of the community underwent changes. The development of Da'wa was no longer centered on the sultanate, but rather it was spread throughout various areas in Langkat, through institutions, individuals, and religious communities. The development of Tarekat Naqsabandiyah Da'wa can still be found today, as evidenced by the presence of many students at the Babussalam pesantren who come from Malaysia. The development of tarekat-based Da'wa has become one of the distinctive characteristics of Malay Islam in Langkat.